ANALISIS STRUKTURAL CERPENYABU NO NAKA KARYA AKUTAGAWA RYUNOSUKE - Yuliando, Herri (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
Yabu no Naka is a short story that tells about seven different testimonies and confessions about a murder of a samurai, Takehiro Kanazawa. This story started with four supporting testimonies of a woodcutter, a Buddhist monk, a police officer, and an old woman. Then followed by major testimonies from the victim and the perpetrator, they are a criminal named Tajomaru, Masago recognition (the wife of a husband who was killed), and the spirits of Takehiro (a samurai) who spoke through an intermediary of a shaman. In analyzing Yabu no Naka, the writer used structural approach, because this short story discussed the elements that build from within. The purpose of this study is to determine the structure of the story, such as the characters and characterization, plot, setting and background, theme, and message of the story in Yabu no Naka. Furthermore, based on the analysis above the writer tried to determine how the relationship between intrinsic elements in the Yabu no Nakashort story so that it creates a unified story. Keywords : Yabu no Naka, Structural, Analysis